Interaction of Title and Text in Functional-Semantic Aspect (by Example of Poem in Prose “Snow” by S. N. Sergeyev-Tsensky) - V. N. Levina; Y. Liu (Научный диалог)
The header component of a literary text is considered as a key to understanding the author’s intention, which is revealed to the reader in getting acquainted with the text of the whole work. It is noted that the title, especially at present, acquires cultural meaning, becoming a cultural code that allows to understand the national specificities of a phenomenon of reality reflected in the text. These and other factors determine the relevance of the study of header components in the context of modern linguistic paradigm. It is shown that the literary text as a reflection of the author’s picture of the world is fertile material for the study of header components. One of the ways to decode the title of the work is semantic analysis of the whole text. By example of the analysis of the poem in prose “Snow” by S. N. Sergeyev-Tsensky the mechanisms of the interaction of title and text in the functional-semantic aspect are revealed. It is argued that the author’s semantics encrypted in the title “Snow” is only revealed based on the analysis of the semantics of the whole text, identification of the symbolic meanings of the key lexeme snow with original landscape semantics. An attempt is made to construct a semantic series, that reveal the meaning of the title of the work “Snow,” which actualize the author’s individual intention, the idea of the work. It is noted that this kind of research opens up possibilities for lexicographical practice, as well as the analysis of the dynamic aspect of the theory of text.